An Information and Marketing System for Agrocomplex Sector Based on Reliable Digital Technology as a Supporting Capacity for Food Security in a Force Majeure Event - Endang Sulistiyaningsih; Valentina Dwi Suci Handayani; Widiastuti Setyaningsih; Wahdan Fitriya; Arif Wahyu Widada; Candra Aryudiawan; Taufan Alam; Imas Masithoh Devangsari (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2021)
The pandemic situation experienced by the world are currently threatening food security in various regions including Indonesia. In these regions, the flow of traffic in the agricultural and fisheries sectors, from the means of production to the distribution of the harvest, is choked up due to social restrictions in various parts of the region. As a strategic step to reduce the impact on the agricultural sector, it is necessary to accelerate information to support the stability of production and also to distribute production results. Digital media in agriculture are needed to provide education with a variety of contents, such as technical production, marketing, and agricultural finance information. The Faculty of Agriculture of Universitas Gadjah Mada (UGM) has supported digital information dissemination through the Desa Apps application. Desa Apps aims to be an application platform that provides agricultural extension and develops digital farmer communities. The information that has been carried out by Desa Apps so far includes agrocomplex sector (agriculture, animal husbandry and fisheries) problems related to cultivation methods and obstacles faced in the land such as attack by plant pest and disease. As a digital media, the Desa Apps has educated farmer and aquaculturists. Optimization needs to be done to improve the performance of Desa Apps as a digital media, one of which is the marketing system that this application actually has. This study evaluates whether farmers and aquaculturists under the auspices of the Faculty of Agriculture are interested in being able to get education and at the same time be able to market their product directly to consumers with one application, the Desa Apps. The findings of the study showed that the pandemic period greatly affected the incomes of the assisted target community, and they required media that can help market their product. The decline in turnover due to pandemic conditions reached 70% with an average decrease of 39.2%. The method of selling products has changed from conventional to online sales by 20% of the total respondents. Changes in sales methods occurred due to distribution limitations due to regional and activity restrictions during the pandemic. Therefore, it is necessary to optimize the Desa Apps application as a digital media to support food security.